Strategi Peningkatan Kinerja Karyawan BTN Syariah KCPS Plered Cirebon - Khamidah; Sri Rokhlinasari; Diana Djuwita (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze the internal and external environment of BTN Syariah KCPS Plered and to identify appropriate strategies for improving employee performance using SWOT analysis. The research employs a qualitative approach with SWOT analysis as the main analytical framework. Primary data were collected through observation, interviews, and documentation, while secondary data were obtained from company records, literature, and journals. The data analysis process involved data collection, data reduction, data presentation, and conclusion drawing. To ensure data validity, a credibility test using source triangulation was applied to examine the issues identified in the research subjects. The results indicate that, internally, the main strengths of BTN Syariah KCPS Plered include competent human resources, an Islamic work culture, and strong managerial support. The identified weaknesses consist of limited continuous training programs, unequal workload distribution, and a less optimal performance evaluation system. Externally, the bank’s opportunities include the increasing public interest in Islamic banking products and supportive government policies, while threats come from intense competition among Islamic banks and fluctuations in national economic conditions. Employee performance improvement strategies at BTN Syariah KCPS Plered are formulated based on the results of the SWOT analysis. The SO (Strength–Opportunity) strategy utilizes internal strengths to seize external opportunities by enhancing service quality and developing innovative Islamic banking products. The WO (Weakness–Opportunity) strategy focuses on improving employee competencies through continuous training and development programs. The ST (Strength–Threat) strategy aims to strengthen customer loyalty amidst growing competition, while the WT (Weakness–Threat) strategy emphasizes maintaining productivity stability through workload management, enhancing supporting facilities, implementing digital monitoring systems, and conducting regular employee coaching.